Implementation of Local Wisdom-Based History Teaching Materials at SMA Muhammadiyah Katingan Tengah - Riskz Abdul Rahman; Jasiah Jasiah; Santiani Santiani (Tarikhuna: Journal of History and History Education, 2025)
This research aims to develop history teaching materials based on local wisdom at SMA Muhammadiyah Katingan Tengah. The focus is on local figures H. Ikap and Minun Dehen, as well as the Dayak tradition of Handep Hapakat. The study employed a descriptive qualitative method, utilizing interviews, observations and documentation studies to understand the implementation of these teaching materials. The findings indicate that integrating local wisdom into history education significantly enhances students' comprehension, motivation and cultural pride. The teaching approach, which includes interactive lectures, group discussions, and field activities, makes the material more contextual and relevant to students' lives. Despite some challenges, such as limited visual media, creative and flexible teaching methods effectively overcome these obstacles. This research highlights the importance of integrating local wisdom to strengthen students' historical understanding, character development, and nationalism, aligning with the principles of the Independent Curriculum (Kurikulum Merdeka).